Draft Annual Plan 1990-91 Government of Karnataka - Planning Commission (Planning Commission, 1991)
The approved outlay for the Seventh Plan was Rs.3575 Crores at 1984-85 prices. At current Prices it is Rs.4025 Crores (the sum of approved outlays for all the Five Annual Plans). Against this, the anticipated expenditure is placed at Rs.4207 Crores. Inspite of resource constraints, the investment in real terms is anticipated to he only slightly less than the envisaged level. The expenditure during the first two years exceeded the approved outlay (see Table-1). The State has proposed (and approved by the Planning Commission) higher outlays for 1987-88 and 1988-89 also, which could not be realised due to resource constraints and the outlays had to be revised downwards.
Planning Department